2008
DOI: 10.1346/ccmn.2008.0560405
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and mineralogical characteristics of French green clays used for healing

Abstract: The worldwide emergence of infectious diseases, together with the increasing incidence of antibioticresistant bacteria, elevate the need to properly detect, prevent, and effectively treat these infections. The overuse and misuse of common antibiotics in recent decades stimulates the need to identify new inhibitory agents. Therefore, natural products like clays, that display antibacterial properties, are of particular interest.The absorptive properties of clay minerals are well documented for healing skin and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 53 publications
4
92
1
1
Order By: Relevance
“…These clays contained concentrations of these elements higher than some cosmetic clays characterized by Abel [38]. The content of theses oxides was similar to those of two French clays used for healing [39]. These results suggested that the Taubaté and Tremembé clays can also be used for this application.…”
Section: [Tabela I -Resultados Da Análise Granulométrica Das Amostrassupporting
confidence: 58%
“…These clays contained concentrations of these elements higher than some cosmetic clays characterized by Abel [38]. The content of theses oxides was similar to those of two French clays used for healing [39]. These results suggested that the Taubaté and Tremembé clays can also be used for this application.…”
Section: [Tabela I -Resultados Da Análise Granulométrica Das Amostrassupporting
confidence: 58%
“…The concentration of these elements in the peloid will depend on their concentration in the mineralmedicinal water and the solid phase (generally clay) used to prepare the peloid. Several authors have described the presence of essential and/or potentially toxic elements in peloids used in spas (Carretero et al, 2010;Karakaya et al, 2010) and in clays with potential for use in pelotherapy (Cara et al, 2000a(Cara et al, , 2000bGomes and Silva, 2001;Vreca and Dolenec, 2005;Williams et al, 2008). However, when considering a potentially useful clay, the concentration of a particular element in the clay or peloid is not as important as its bioavailability, that is, the concentration of the element which could enter the body of the patient during application of the peloid.…”
Section: Comparison With Peloids Used In Spasmentioning
confidence: 99%
“…The extent of adsorption is determined by the chemistry of the clay minerals, exchangeable ions, the surface properties (Williams et al, 2008) and the fine structure of clay particles (Hassen et al, 2003). An important role is also played by pH, dosage and exposure time (Brouillard and Rateau, 1989).…”
Section: Adsorption Capacity and Effects Of Clay Mineralsmentioning
confidence: 99%